AN INVESTIGATING INTO THE TYPOLOGY OF IRON AGE MEGALITHS IN THE KRISHNAGIRI DISTRICT OF TAMIL NADU - R. Soubhagya; P. Venkateswaran (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In general, the burial monuments constructed with huge stones are called Megaliths. They can be either Sepulchral or Memorial. Universally, Megaliths represent a culture that developed during the Neolithic period and prevailed in the Chalcolithic Ages. In the Indian context, recent studies provide ample evidences to prove that in the southern part of the country, particularly in Tamil Nadu, the Megaliths evolved around 2000 BCE in the Pre-Iron Age context and thrived through the successive cultural phases of the Iron Age and early Historic period. Various kinds of megalithic structures have been observed in this study. Krishnagiri is an archaeologically rich district in Tamil Nadu. The antiquity of the district goes back to the Upper-Paleolithic age and exhibits a continuous Prehistoric culture, including such as the Mesolithic, Neolithic, Iron ageand Proto-historic ages. Megalithism is a cultural phase that occurred in the Iron and Proto-historic ages. Although Tamil Nadu was exposed to pre-Iron Age Megalithic site, scientific dates were needed to establish their presence in the Krishnagiri district. This chapter attempts to understand the typology of Megalithic monuments based on extensive explorations. Since only two excavations, Mayiladumparai and Oramanagunta, were carried out in the district of Megaliths, the article mostly depends the observations of the disturbed monument. Basic types, such as Cairn circle, Stone circle, Dolmen, Dolmenoid Cist and Menhir were found in the district, along with their variants classified as sub-types in addition to the Pit, Urn, and Sarcophagus. Labyrinths are an important Iron Age monument and that could be the regional-specific in Tamil Nadu. This paper also discusses the features of Mallachandram type regional specific Dolmens, the Portholes and Cup marks, which are characteristic features of Megaliths.